Amorphous/crystalline heterostructured nanoporous high-entropy metallic glasses for efficient water splitting - Meng Liu; Shoucong Ning; Dongdong Xiao; Yongzheng Zhang; Jiuhui Han; Chao Li; Anmin Nie; Xiang Zhang; Ao Zhang; Xiangrui Feng; Yujin Zhang; Weihua Wang; et al. (Materials Futures)
Developing nanoporous high-entropy metallic glass (HEMG) with a high specific surface area presents a promising approach to develop a cost-effective and efficient catalyst, which utilize the synergistic effect of its multi-component composition and the adjustable atomic environment of its disordered structure. However, the glassy structure invariably gets erased due to the inevitable crystallization during the nanoporous construction procedure through dealloying. Here, an innovative HEMG with an endogenetic nano-scale phase-separated structure is specially designed to maintain a fully glassy state throughout the nanoporous construction procedure. Consequently, an amorphous/crystalline heterostructure (ACH)—nanocrystal flakes embedded in amorphous ligaments—is intentionally constructed, which exhibits significant lattice distortion at amorphous/crystalline interfaces, resulting in high density of active sites. The ACH facilitates intermediate adsorption by promoting directional charge transfer between amorphous and crystalline phases and improves product desorption through downshifting the d-band center. This results in remarkable electrolysis performance, requiring only a 1.53 V potential to achieve a current density of 10 mA cm ^−2 for overall water-splitting in an alkaline electrolyte, surpassing that of commercial Pt/C || IrO _2 catalysts of 1.62 V. This research pioneers strategies to refine the composition, atomic structure, and electron characteristics of HEMG, unlocking new functional applications.